MYTHOLOGICAL CONSCIOUSNESS, MYTH, RITUAL: METHODOLOGICAL WAYS OF RESEARCHING - Васильєва, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Methodological ways of researching in mythological consciousness, myth, ritual are being analyzed in this article.